Do Tourists Prefer Malaysia as Preferred Festivity Location? Effect of Service Quality, Preceived Value and Trust on Destination Loyalty and Intention to Revisit (S/O 13281) - Nadarajah, Gunalan (UUM, 2020)
The study focuses on examining the effects of service quality, perceived value and trust on destination loyalty and intention to revisit amongst international tourists in Malaysia, in which a survey was conducted to collect data from the targeted population. The targeted population of this study comprises of international tourists during festivals in Malaysia. Festivals included for the study are only the ones organized by Tourism Malaysia in 2016 thus population consists of international tourists who visited festivals organized by Tourism Malaysia in 2016. Selected respondents were 20 years old and above. This is to ensure the accuracy and maturity of responses acquired.